Optimization of EDM Injection Flushing Type Control Parameters Using Grey Relational Analysis on AISI 304 Stainless Steel Workpiece - Mohamed Reza Zalani, Mohamed Suffian; M. A., Hamdi; Azmir, Azhari (Universiti Malaysia Pahang, 2010)

(untitled)
This paper deals with optimization of Electrical Discharge Machining (EDM) Injection flushing type control parameters on multi-performance optimization characteristics instead of single performance optimization using Grey Relational Analysis (GRA) Method. The experimental control parameters were being optimized according to their various machining characteristics namely material removal rate (MRR), electrode wear ratio (EWR) and surface roughness (SR) using copper as the tool and AISI 304 stainless steel as the workpiece. This parameters optimization was based on Taguchi’s orthogonal array (OA) combined with GRA. A grey relational grade (GRG) calculated based on GRA was used to optimize the EDM process with multiple performance characteristics and Taguchi’s L18 OA was used to plan the experiments. The machining parameters selected are polarity, pulse on duration, discharge current, discharge voltage, machining depth, machining diameter and dielectric liquid pressure. Results shown that machining performance was improved effectively using this approach. The predicted responses at optimum parameter levels are in good agreement with the results of confirmation experiments conducted for verification tests.